The 'second-codon rule' and autophosphorylation govern the stability and activity of Mos during the meiotic cell cycle in Xenopus oocytes. - Nishizawa, M (1992)
The c-mos proto-oncogene product, Mos, functions in both early (germinal vesicle breakdown) and late (metaphase II arrest) steps during meiotic maturation in Xenopus oocytes. In the early step, Mos is only partially phosphorylated and metabolically unstable, while in the late step it is fully phosphorylated and highly stable. Using a number of Mos mutants expressed in oocytes, we show here that the instability of Mos in the early step is determined primarily by its penultimate N-terminal residue, or by a rule referred to here as the 'second-codon rule'. We demonstrate that unstable Mos is degraded by the ubiquitin-dependent pathway. In the late step, on the other hand, Mos is stabilized by autophosphorylation at Ser3, which probably acts to prevent the N-terminus of Mos from being recognized by a ubiquitin-protein ligase. Moreover, we show that Ser3 phosphorylation is essential for Mos to exert its full cytostatic factor (CSF) activity in fully mature oocytes. Thus, a few N-terminal amino acids are primary determinants of both the metabolic stability and physiological activity of Mos during the meiotic cell cycle.